Clinical effectiveness of trimetazidine as a leading cardiovascular drug with metabolic action - A. Yu. Gasparyan; A. H. Petrosyan; L. M. Ayvazyan (Кардиоваскулярная терапия и профилактика)
Trimetazidine is proved to be a highly effective metabolic agent, compared to other drugs with the same action. Trimetazidine shifts cardiac energy metabolism from fatty acid oxidation towards glucose oxidation by inhibiting mitochondrial long-chain 3-ketoacyl-coenzyme A thiolase. In a number of randomized controlled trials, trimetazidine was shown to improve the ergometric exercise capacity and total workload, to reduce angina attacks and nitroglycerin total dose in patients with coronary heart disease, heart failure, and after coronary artery bypass graft surgery. It is especially important that trimetazidine is highly effective in diabetes-associated cardiac pathology. Clinical effectiveness of other metabolic agents is also discussed, and directions for further research are presented, based on evidence-based data analysis.